Après les retraites massives dans deux hôpitaux québécois : enjeux des rapports entre générations différentes de travailleurs - Solange Lefebvre (Perspectives Interdisciplinaires sur le Travail et la Santé)
As regards research on health and security in the workplace, the relationships among various generations of workers require further study. One crucial point is the transmission of knowledge and skills that may affect the health of workers or, possibly, those in their care. These subjects are broached in a case study pursued in 1998 in two hospitals of the Montreal region following the wave of early retirement cases in 1997 and the arrival of numerous newly hired employees. The negative impact has been found to vary according to the unit and work quarter studied. The value of experience with regards to nursing skills has been recognized ; it is clear that the theoretical knowledge of the newly hired employees must be combined with experience. It has also been shown that organizational strategies have left little room for any exchange, which is left to the informal initiatives of the workers themselves. As regards health and security, it has been found that anxiety and stress among employees are an important factor, and that the risks run by patients left in the care of inexperienced employees and without adequate surveillance remain a concern.